2021
DOI: 10.1002/etc.5076
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion and Toxicity of Polystyrene Microplastics in Freshwater Bivalves

Abstract: The ubiquity of microplastics in aquatic ecosystems has raised concerns over their interaction with biota. However, microplastics research on freshwater species, especially mollusks, is still scarce. We, therefore, investigated the factors affecting microplastics ingestion in the freshwater mussel Dreissena polymorpha. Using polystyrene spheres (5, 10, 45, 90 µm), we determined the body burden of microplastics in the mussels in relation to 1) exposure and depuration time, 2) body size, 3) food abundance, and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 55 publications
1
9
0
1
Order By: Relevance
“…Diatomite has been used as natural reference material in previous microplastics studies. In the freshwater mollusks Dreissena polymorpha and Lymnea stagnalis, diatomite was in general not more toxic than polystyrene microplastics (Weber, Jeckel, et al 2021;Weber, von Randow, et al 2021) but induced a stronger effect on the antioxidant capacity in the former species (Weber, Jeckel, and Wagner 2020) at identical numerical concentrations. In Chironomus riparius larvae, diatomite was toxic but less so than polyvinyl chloride microplastics at identical mass-based concentrations (Scherer et al 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Diatomite has been used as natural reference material in previous microplastics studies. In the freshwater mollusks Dreissena polymorpha and Lymnea stagnalis, diatomite was in general not more toxic than polystyrene microplastics (Weber, Jeckel, et al 2021;Weber, von Randow, et al 2021) but induced a stronger effect on the antioxidant capacity in the former species (Weber, Jeckel, and Wagner 2020) at identical numerical concentrations. In Chironomus riparius larvae, diatomite was toxic but less so than polyvinyl chloride microplastics at identical mass-based concentrations (Scherer et al 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, ingestion of MPs allocates a pathway for the metal transfer to organisms (Naqash et al 2020). However, this is species dependent; as in the experimental exposure to MPs in mussels, it was found that mussels can excrete most microplastic particles within a certain period of time, and that the burden of MPs in large mussels is much less than that in small mussels (Weber et al 2021).…”
Section: Ps On the Absorption Of As CD And Pb By Clamsmentioning
confidence: 99%
“…1,2 The potential toxicity and health effects of MPs have attracted significant research attention. 3,4 The toxicokinetic behavior of pollutants is important for understanding their occurrence and toxicity development in organisms. 5,6 Therefore, the toxicokinetics of MPs and how they may bioaccumulate within organisms have become a critical scientific and practical issue due to the potential health effects of MPs.…”
Section: Introductionmentioning
confidence: 99%